The transformation and design of EU restrictive measures against Russia. Issue 3 (3rd April 2023) - Meissner, Katharina; Graziani, Chiara
ABSTRACT: Sanctions were the European Union's (EU) immediate response to Russia's invasion of Ukraine on 24 February 2022. These restrictive measures focus on specific individuals, entities, goods, services, and sectors. Out of a need for nuanced data, we map and analyze the entire set of EU sanctions imposed on Russia since 2014 until today. We show and argue that the sanctions' design has become increasingly comprehensive over the past months which reflects the EU's geopolitical considerations in carving out a response to the unparalleled threat imposed by Russia. Our new, author-created dataset covers the complete track record of Council decisions, regulations, and annexes of these restrictive measures, and thereby offers fine-grained information on the transformation and design of EU sanctions against Russia and the Russian-controlled areas in Ukraine.